L’Inde en Afrique ou l’impossible rattrapage vis-à-vis de la Chine - Xavier Aurégan (L'Espace Politique)
Since the Conference of Bandung in 1955, the ambition to become a key player in international relations characterized both Indian and Chinese governments. To achieve this international status, New Delhi and Beijing rely on Africa. In order to evaluate the current Chinese and Indian presences in Africa and their intervention modalities, this article is based on field studies in West Africa (Sino-African relations), as well as primary and secondary sources in both cases. On the African continent, economic (investments), commercial and cultural (leadership, diaspora, cultural centers or African students), then political (development assistance and cooperation, embassy networks and relations) and institutional (cooperation forums) analysis factors express the supposed Indian backwardness vis-à-vis the Sino-African dynamic relationship. These factors may help to establish the potential India's marginalization in Africa. Nevertheless, in this complex maze of globalization, the New Delhi authorities have undeniable assets that would be likely to develop and entrench an African policy.